Anaesthesia For ECT In Neuroleptic Malignant Syndrome - What Is Ideal? - Baskaran, Priyaneka; Santhirasegaran, Jaishree; @ Julaihi, Norhuzaimah Bt Julai (Bali Journal of Anesthesiology, 2017)
We report a case involving a 46 year old male with schizophrenia who presented with fever, inability to speak, sialorrhoea, limb stiffness, profuse sweating, tremors and rigidity of bilateral upper and lower limbs following an increase in dosage of his antipsychotics.Â  A provisional diagnosis of neuroleptic malignant syndrome (NMS) was made based on the Levensen criteria. His anti psychotics were promptly discontinued and he was transferred to ICU for critical care support. We utilised lorazepam and prescribed bromocriptine and his NMS symptoms improved. However, in view of residual catatonic symptoms, decision was made to commence ECT. A combination of rocuronium sugammadex was used successfully in all his ECT procedures and found to be an excellent alternative to succinycholine in this patient.